2008
DOI: 10.1136/jnnp.2007.143420
|View full text |Cite
|
Sign up to set email alerts
|

Narcolepsy in Southern Chinese patients: clinical characteristics, HLA typing and seasonality of birth

Abstract: In our Southern Chinese narcolepsy series, bi-modal peak pattern of age of onset, excess winter birth and tight association of HLA DQB1*0602 with cataplectic narcolepsy were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
3
12
1
1
Order By: Relevance
“…This is in comparison to adults, who may have greater compensatory mechanisms (e.g., drinking caffeinated beverages). In a study conducted in South China, N+C was found to have a bimodal distribution, with the first peak at age 11 coinciding with that found in our review, and the second peak at age 39 95 . However, in the N-C group only one peak at about age nine years was found 95 .…”
Section: Resultssupporting
confidence: 85%
“…This is in comparison to adults, who may have greater compensatory mechanisms (e.g., drinking caffeinated beverages). In a study conducted in South China, N+C was found to have a bimodal distribution, with the first peak at age 11 coinciding with that found in our review, and the second peak at age 39 95 . However, in the N-C group only one peak at about age nine years was found 95 .…”
Section: Resultssupporting
confidence: 85%
“…21,22 We observed a peak in symptom presentation during the age period of 10-15 years with diminishing frequency with age and a second slight increase in presentation between the ages of 35 and 40 years. We did not observe a gender difference in the bimodal character of age at which symptoms presented, and therefore could not explain its contribution to the observed gender difference in time to diagnosis.…”
Section: Menmentioning
confidence: 67%
“…As most local Chinese patients were reluctant to undergo lumbar punctures, there were limited data available on CSF hypocretin-1. 3 In our previous family study, we identified a group of relatives with narcoleptic spectrum (unaffected) who had one or more SOREMPs on MSLT but did not fulfil the diagnostic criteria of narcolepsy. 3,14,15 Another group of relatives who were diagnosed with narcolepsy (affected) were included into the 2 narcoleptic groups.…”
Section: Study Design and Subject Recruitmentmentioning
confidence: 99%
“…Those cases who had clinical follow-up assessments of NPSG and MSLT were included in the second part of the study. All the subjects had signed relevant informed consents of the respective studies, 3,14,15 which were approved by the institutional ethics committee.…”
Section: Study Design and Subject Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation